Power and rents - political influence on rent extraction: Quasi-experimental evidence for Bavaria - Lukas Schötz (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2016)
The pursuit of individual rents by political representatives is recognized as one of the major shortcomings of political systems. While both legal and illegal types of rents are distributed by political decisions, research has focused primarily on illegal rent-seeking by politicians. This article examines the extent to which elected Bavarian mayors are provided with legal political rents. As independently elected councils determine the remuneration of mayors in Bavarian municipalities, an examination of this process is used to determine whether evidence exists that strong political competition limits rent allocation in the political system. Results from this quasi-experimental regression discontinuity design (RDD) approach show that political competition and party considerations have a significant impact on the allocation of legal rents to local leaders. However, this effect is not present in cases where rents received by mayors were already high prior to the election.
Keywords: 330; political rents; local affairs; regression discontinuity design